2021
DOI: 10.17977/um064v1i102021p1341-1357
|View full text |Cite
|
Sign up to set email alerts
|

Perancangan Game 3D sebagai Pengenalan Lingkungan Kampus Universitas Negeri Malang

Abstract: The State University of Malang as one of the largest universities in the city of Malang has various faculties, departments and study programs. The number of study programs is certainly supported by the many facilities owned to support academic and non-academic activities. This article aims to create interactive media that can be used to introduce the environment and facilities owned by the Malang State University campus to students and the wider community. Especially with the current Covid-19 pandemic, this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Untuk melengkapi media promosi dan informasi yang sudah ada, perlu di buat sebuah media baru yang berbeda yaitu media baru yang memungkinkan masyarakat untuk bisa menjelajahi kampu UM secara virtual dan interaktif salah satunya melalui aplikasi game. Lalu perancangan ini disebar luaskan melalui berbagai media sosial dengan target media utama yaitu website Universitas Negeri Malang atau akun sosial media yang berada di naungan universitas negri malang, dengan bantuan software blender 3D [11]. Penelitian berjudul Pengenalan Kampus II Universitas Muhammadiyah Sidoarjo melalui Game Controller oleh Ramadhani Sugyono.…”
Section: Penelitian Sejenisunclassified
“…Untuk melengkapi media promosi dan informasi yang sudah ada, perlu di buat sebuah media baru yang berbeda yaitu media baru yang memungkinkan masyarakat untuk bisa menjelajahi kampu UM secara virtual dan interaktif salah satunya melalui aplikasi game. Lalu perancangan ini disebar luaskan melalui berbagai media sosial dengan target media utama yaitu website Universitas Negeri Malang atau akun sosial media yang berada di naungan universitas negri malang, dengan bantuan software blender 3D [11]. Penelitian berjudul Pengenalan Kampus II Universitas Muhammadiyah Sidoarjo melalui Game Controller oleh Ramadhani Sugyono.…”
Section: Penelitian Sejenisunclassified
“…Alpha tests or testing were carried out and gave results that the game could run quite well even though it was not perfect. From the beta testing results, it was found that when the game was run on a computer with general specifications with very lowquality settings, the game was able to run very well [7]. The development of games to serve as a campus introduction media has also been carried out at the Muhammadiyah Sidoarjo University (UMSIDA) campus.…”
Section: Introductionmentioning
confidence: 99%